Global Offshoring Of Services:Sustaining Competitive Advantage In Developing Countries - The Malaysian Case - Selvadurai, Shanker (2005)
The increasing tradability of services enabled by developments in information and communication technologies and by growing liberalisation of trade has created an industry based upon the decoupling and relocation of service activities to foreign countries. Estimated above $40 billion in 2003, the offshoring of services to emerging markets is expected to grow at 30 percent annually from 2003 to 2008. Increasingly, firms are offshoring activities to foreign affiliates or third party service providers in order to protect or advance their competitiveness through cost reduction, quality improvement and market growth. Recognising the potential for pushing national and skills development, a number of developing countries, including Malaysia, have made it a key priority to attract inward investment by foreign multinationals for projects related to the offshoring of services. Through qualitative research by means of interviews with multinationals having located offshore activities in Malaysia and review of literature related to trade, investment, national competitiveness and human capital theories; this study explains the relationship between the types of service activities offshored, business drivers for offshoring service activities, locational determinants for offshoring and the suitability of available human capital to meet offshoring requirements. A framework for national competitiveness in the global offshoring of services is developed and used to describe how public policy can influence the primary drivers of competitiveness – business environment, infrastructure, education and training – to stimulate the essential conditions – wages and costs, productivity, human capital quality – necessary for sustainable competitive advantage.